Photocatalytic hydrogen generation by WO3 in synergism with hematite-anatase heterojunction. (31st July 2020) - Jineesh, P.; Bhagya, T.C.; Remya, R.; Shibli, S.M.A.
Abstract: The present study reports about exploration of a multi-component photocatalytic system comprising of WO3, TiO2 and Fe2 O3 with tandem n-n heterojunctions. The ternary WO3 /TiO2 /Fe2 O3 nanocomposite with WO3 nanoparticles over the interfaces of Fe2 O3 and TiO2 is synthesized by wet precipitation followed by thermal decomposition. The WO3 /TiO2 /Fe2 O3 nanocomposite has an enhanced photocatalytic performance towards hydrogen generation by water splitting reaction under visible light irradiation, when compared to the Fe2 O3 /TiO2 system. A band gap of 2.10 eV, favouring visible light absorption was achieved with the distribution of WO3 nanopartcles over the interfaces of Fe2 O3 and TiO2. The as prepared WTF heterojunction exhibited a maximum hydrogen production rate of 10.2 mL h −1 for a catalyst loading of 0.025 g mL −1 . The enhanced photocatalytic performance is tested in presence of various sacrificial agents and proton source. In both cases, the higher photocatalytic efficiency is attributed to the more visible light harnessing ability and pronounced charge separation owing to the tandem n-n heterojunctions generated between TiO2 with WO3 and TiO2 with Fe2 O3 semiconductors and enhancing the lifetime of the photogenerated electron-hole pairs. Graphical abstract: Image 1 Highlights: Ternary WO3 /TiO2 /Fe2 O3 nanocomposite with tandem n-n heterojunctions was synthesized. The multilane upgraded the charge transfer pathway at the tandem n-n heterojunctions. WO3 boosted the synergism of heterojunctions, augmented swift transfer of electrons. Photocatalytic H2 generation rate of the WO3 /TiO2 /Fe2 O3 was significantly enhanced.